Piper betle Leaf Extract Spray Gel for Diabetic Wound Causes by Bacterial Infections - Wulandari, Ririn Lispita; Aljufri, Achmad Quraisy; Chafiffa, Safira; Andani, Geges Arstri (Indonesian Journal of Pharmaceutical Science and Technology, 2025)
Antibiotic resistance in the treatment of diabetic wound infections is common. Piper betle leaf extract has antibacterial, anti-inflammatory, and antioxidant activities. This study aims to formulate a spray gel from Piper betle leaf extract and test its effect on diabetic wounds infected with Methicillin-Resistant Staphylococcus aureus (MRSA) and Pseudomonas aeruginosa. The gel was made with 10% (F1), 15% (F2), and 20% (F3) extracts. The organoleptic physical characteristics, pH, homogeneity, viscosity, spray pattern, adhesive spreadability, drying time, and physical stability were tested. All rats were given alloxan 170 mg/kgBW, fasting glucose levels were measured, and then grouped into control, MRSA-exposed, and P. aeruginosa-exposed groups. The negative and positive controls were also included in the test. A 2 cm wound with a depth of 0.3 cm was given bacteria, except for the normal control. The length of the wound was measured, and the wound reduction was calculated as a percentage of wound closure and statistically analyzed. All the formulas met the physical criteria, significantly closing MRSA wounds by 100%. F2 and F3 significantly closed P. aeruginosa wounds by 89.88% and 93.13%, respectively. Collectively, the Piper betle leaf extract spray gel had an effect that could relieve diabetic wound infections.